Keyakinan yang mendukung tindak kekerasan perundungan berdasarkan perspektif perbedaan jenis kelamin - Ihsana Sabriani Borualogo; Sulisworo Kusdiyati; Hedi Wahyudi (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2023)
Previous studies on bullying revealed the high frequency of bullying incidents in West Java Province. Bandung is among the highest bullying incidents rate in West Java. This study aimed to explore the contribution of beliefs supporting violence to bullying in boys and girls. Beliefs supporting violence is one of the bullying predictors, but there is still limited study exploring beliefs supporting violence in Indonesia from the perspective of gender differences. This study used a cross-sectional design. A representative sample of elementary and junior high school students in Kota Bandung (N = 1,539) was obtained from a stratified cluster random sampling technique. There were 53.2% girls and 46.8% boys. Belief supporting violence instrument and bullying perpetration instrument that have been adapted into Indonesian were used in this study. Data were analyzed using linear regression. Beliefs supporting violence contributed significantly to physical bullying in girls (β = 0.182; p = 0.000) and boys (β = 0.141; p = 0.000), verbal bullying in girls (β = 0.248; p = 0.000) and boys (β = 0.247; p = 0.000), and psychological bullying in girls (β = 0.110; p = 0.002) and boys (β = 0.085; p = 0.023). The socio-ecological theory from Bronfenbrenner was used to explain the results. Beliefs supporting violence contributed significantly to bullying perpetration in boys and girls. Boys have higher mean scores on beliefs supporting violence compared to girls. However, gender did not moderate beliefs supporting violence to bullying perpetration. Parents and teachers shall consider any violent incidents caused by beliefs supporting violence that predict school bullying incidents. This cautious hopefully will help to decrease the number of bullying perpetration cases.